Fracture Detection in the Carbonate Baba Formation, Bai Hassan Oilfield, Northern Iraq, Using Conventional Well Log Data - Sadeq, Qays M.; Baban, Dler H.; Shwani, Ayub M. Ahmed; Barzinji, Sabir S. (Journal of Petroleum Research and Studies, 2024)
One of many lengthy, asymmetrical, and double plunging anticlines that make up the Foothill part of the Unstable Shelf Zone in northern and eastern Iraq is the Bai Hassan Oilfield. The absence of advanced fracture detection tools such as the Formation Micro Image (FMI) log and Televiewer tools used in boreholes has led to the follow of new methods to use common and ordinary well logging methods to investigate possible fractures in the reservoir. For fracture detection in the Baba Carbonate Formation in the Bai Hassan Oilfield, Northern Iraq, this study employs conventional well log data from two chosen wells (BH-101 and BH-078). Several applications have been combined, including the tri-porosity cross plot (M-N), secondary porosity calculation, natural gamma ray spectroscopy (NGS), dual laterolog - microspherical focused logs separation, and the cementation exponent (m) parameter, for detecting the fractured zones of the formation. The scatter of the sample points towards the secondary porosity field of the M-N crossplot was a preliminary indication for the existence of fractures in the studied sections. In various horizons of both studied wells, the Baba Formation has good secondary porosity that ranges from less than 1.0 to about 10%. Almost the entire formation has certain percentages of secondary porosity, especially in its middle and lower parts. An increase in the Uranium volume, as observed in some horizons from the U/K and U/Th ratios, coincides with the calculated secondary porosity values and supports those zones being fractured zones. The relative decrease in resistivities recorded by the resistivity logs in certain horizons also supported the suggestion that those intervals were fractured zones. The formation appeared to have cementation exponent values of 1.59 in the well BH-101 and 1.71 in the well Bh-078; both values are related to formations with fractures. It is vital and recommended that the procedure used in this study be applied to boreholes with image logs in order to calibrate the results and the reliability of the identified fracture zones.